Microstructural evolution, mechanical and thermophysical properties of (TiZrNbTa)(C1-xNx) multi-component carbonitrides - Ming Li; Wen Zhang; Ziheng Chen; Fangwang Fu; Jinyong Zhang; Lin Ren; Fan Zhang; Weimin Wang; Zhengyi Fu (Journal of Materials Research and Technology)
A series of multi-component carbonitrides (TiZrNbTa)(C1-xNx) (x = 0, 0.1, 0.2, 0.3, 0.4, 0.5) were successfully synthesized via spark plasma sintering (SPS) at 2000 °C under 35 MPa for 10 min. The effects of nitrogen content on microstructure, mechanical properties and thermal performance were systematically investigated. The results demonstrate that the nitrogen incorporation induces lattice distortion in the non-metallic sublattice, significantly reducing porosity and enhancing the densification process, while exhibiting negligible influence on the average grain size. Moreover, moderate nitrogen doping optimizes the mechanical properties, whereas excessive doping proves detrimental. The MCC8N2 sample (x = 0.2) demonstrates optimal mechanical performance, exhibiting a flexural strength of 768 ± 17 MPa, fracture toughness of 6.2 ± 0.3 MPa m1/2 and Vickers hardness of 20.6 ± 0.2 GPa. Furthermore, the nitrogen incorporation effectively reduces the thermal conductivity through intensified lattice distortion and enhanced phonon scattering. The MCC5N5 sample (x = 0.5) displays the thermal conductivity of 11.65 W m−1 K−1 at 373 K and 30.27 W m−1 K−1 at 1373 K. These findings highlight the significant potential of (TiZrNbTa)(C1-xNx) carbonitrides for high-temperature thermal insulation applications.